The Implementation of the Discovery Learning Model Assisted by Snakes and Ladders Media on Students’ Learning Outcomes in Mathematics for Grade 1 at SDN 07 Koto Baru - Ratnawati; Raimon Efendi; Nursya Fitri (Lembaga Penerbitan dan Publikasi Ilmiah Yayasan Pendidikan Tumpuan Bangsa, 2025)
This research was motivated by the suboptimal implementation of mathematics learning. The learning process had not yet utilized appropriate models or media, resulting in many students' learning outcomes falling below the Minimum Mastery Criteria (KKM). To address this, the researcher conducted a study using the Discovery Learning model assisted by Snakes and Ladders media. The purpose of this research was to determine the effect of the Discovery Learning model assisted by Snakes and Ladders media on students’ learning outcomes in mathematics, specifically Chapter III: Measuring the Length of Objects, at SDN 07 Koto Baru. This study employed an experimental research method with a one-group pretest-posttest design. The population consisted of all first-grade students at SDN 07 Koto Baru. The sample was determined using a saturated sampling technique, resulting in a total of 21 students. Data collection was carried out using pre-tests and post-tests. The study was conducted in the second semester of the 2025 academic year. Based on the results of the paired samples t-test, a significance value of 0.000 < 0.05 was obtained. It can be concluded that the Discovery Learning model assisted by Snakes and Ladders media had a significant effect on students’ learning outcomes in mathematics, particularly in Chapter III on measuring object length for first-grade students at SDN 07 Koto Baru. The findings indicate that this model provides a positive impact on students' mathematics learning outcomes. Moreover, the Discovery Learning model supported by Snakes and Ladders media can be used by teachers to connect learning material with students’ real-life experiences, increase engagement, foster active learning, and improve academic performance.